(3UjZ GdYbhO hGdEjbGYGJs - (3GdMGQKj GdYGedj GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s ((3JGL GdOjf eMeO Hf eQJVi GdYGedjs)
(3ChdgG (B:s
(3GdMeO ddg MeOG cKjQG (B.. (3agPg LedI cGajI aj HjGf UjZ GdYbhO hGdEjbGYGJ EPG cGf dGHO ef eYQaJgG def GMJGL Edi TjA efgG ef Gdecdajf dJhba MUhdg dCehQ GdeWdb Hg efgG TQYG Ydi GdEJjGf (B...s
(3BNQgG (B:s
.. (3hEf CWdb aaj chfg EbQGQ bhdGf CUMgeG fYe hdh CHge GdEbQGQ aj TjFjf WhdH HGdHjGf hdh CbQ HdaX efge agh CfhGY hdh GSJKfi ef ebQHg adg CbSjGe Ch CMcGe hLejY Pdc ePchQ (B..... (3aGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/102s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis